LANGUAGE STYLES IN THE JAKARTA POST HEADLINES ABOUT COVID-19 - Viena Rara Alvenia; Lili Awaludin; Toneng Listiani (ReALL - Research on Applied Linguistics and Literature, 2023)
Language style is a variety of language caused by differences in language situations or differences in the relationship between the speaker (writer) and listener (reader) (Joos, 1976). The purposes of this research are: 1) to identify the types of language styles used in The Jakarta Post headlines about COVID-19 and 2) to analyze the function of language styles in The Jakarta Post headlines about COVID-19. This research was analyzed using Joos's theory as the basis of analysis. Joos (1976) said that there are five types of language styles; 1) frozen style, 2) formal style, 3) consultative style, 4) casual style, and, 5) intimate style. The object used in this research is from The Jakarta Post newspaper. The researcher uses a qualitative case study to analyze this study. The steps of analyzing data are determining the criteria of each category, matching each data which fits the types of language styles, and describing the function of language styles in The Jakarta Post headlines. Based on the result of the analysis, the researcher found 108 data on the types of language styles, there are 8 data of frozen style and 100 data of formal style. In addition, the researcher takes 20 pieces of data to describe the function of language style in The Jakarta Post headlines about COVID-19. This research concludes that The Jakarta Post headlines dominate with formal style and frozen style in conveying the topic. Because, the topic of Covid-19 is talking about serious things, therefore using the frozen and formal styles is more suitable than the other styles.